Integrating Islamic Fintech and Smart Contracts for Enhancing Governance in Waqf Asset Management - Wan Haniff, Wan Amir Azlan; Yasin, Redwan; Mohd Yusoff, Rahmawati; Ab Halim, Asma Hakimah; Markom, Ruzian; Abd Rashid, Aiman Hafiz (Advances in Social Sciences Research Journal, 2025)
The article investigates the challenges and prospects of the ruling of Waqf Crowdfunding (Waqf-CF) scheme adoption in Malaysia as Shariah-compliant fintech successors deployed to mobilize Islamic endowment. However, the implementation of Waqf-CF is hindered by a number of challenges, such as the uncertainty of the legal aspects and fragmented governance, along with technology limitations and Shariah compliance issues. Using a qualitative approach, insights were gathered from seven experts 7 experts in finance, academia, and business to inform and guide our work. The results suggest that poor coordination of regulation between federal and state governments, varied modes of governance, and a lack of fintech literacy in waqf bodies are the barriers to successful implementation. In this regard, the paper examines the Waqf-CF models currently being used, including the Crowdfunding-Waqf Model and the Hasanah Platform, by highlighting the pros and cons of each. Based on these, the authors present a sophisticated hybrid model combining blockchain-based smart contracts, AI-led risk profiling, and real-time Shariah auditing for increased trust, transparency, and scalability. Finally, the paper calls for the need of a national regulatory framework and better institutional support to drive Waqf Crowdfunding as an ethical and sustainable funding option that is in line with Maqasid al-Shariah and the nation’s vision to be a global Islamic financial hub.